El acompañamiento vocacional en el Movimiento Juvenil Salesiano de las Hijas de María Auxiliadora de Santiago de Chile desde un enfoque Antropológico Espiritual - Toro Vergara, Alejandra del Rocio (2015)
This thesis, which subject is the Attendance of Vocations in the Salesian Youth Movement of The Institute of Hijas de María Auxiliadora of Santiago de Chile, from an anthropological-spiritual focusing, has found showing such method in the different analyzed education communities. The development of this work has involved to support, theoretically, the subject learned, being compared with the existent reality in the education communities of Hijas de María Auxiliadora in Santiago de Chile, through a qualitative methodology, which being inductive, known as the establishment of theory from the analyzed phenomenon; it allows to gather, analyze and interpret the obtained data, from implements of a summary of information. At the same time, the development itself appears as the keys of discernment, sense of life, project of life, from which is possible to search about the Attendance of Vocations, fundamental point of anthropological-spiritual of each person.